The Effect of Character Education and Humanistic Spirit on K3 Culture (Study at Pamulang University) - Rahmi Hermawati; Eni Puji Astuti; Rima Handayani; Denok Sunarsi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study was to determine the effect of character education and humanistic spirit on K3 culture (study at Pamulang University). This research is a causal quantitative study (causation by processing numerical data), using survey methods by collecting data through distributing questionnaires to university students. Pamulang Management Study Program this research uses the Multiple Linear Regression Analysis method using a test tool in the form of SPSS. The results of the study show the influence of character education and the human spirit on OSH culture. The R value (correlation) is 0.816 and the R Square value (determination) is 0.666 indicating that the Y variable (K3 culture) is influenced by the X1 variable (character education) and the X2 variable (humanist spirit) together, amounting to 66.6% and the remaining 33.4% is influenced by other factors not examined.